A Role for Collapsin-1 in Olfactory and Cranial Sensory Axon Guidance - Kobayashi, Hiroaki (J Neurosci, 1997)
Collapsin-1 is a member of the semaphorin family of signaling molecules that acts as a repellent for growing spinal sensory axons. We have constructed a chimeric collapsin-1/alkaline phosphatase probe to visualize putative collapsin-1 receptors in vitro andin situ. As predicted by the activity profile of collapsin-1, the probe binds spinal sensory tracts, ventral spinal roots, and the sympathetic chain but does not bind retinal axons. In addition, we find that the probe binds sensory axons arising from the olfactory epithelium and some, but not all, cranial sensory nerves. As predicted by these binding studies, in vitro assays demonstrate that primary olfactory sensory, trigeminal, and jugular ganglion growth cones collapse in the presence of soluble collapsin-1. Comparing the expression pattern of collapsin-1 with the trajectories of collapsin-1 responsive axons suggests that in both the spinal cord and the olfactory bulb, collapsin-1 prevents premature entry of sensory axons into their target and helps determine the final location of sensory terminations.